Understanding phosphoinositides: rare, dynamic, and essential membrane phospholipids - Dickson, Eamonn J; Hille, Bertil (Biochemical journal, 2019)
Polyphosphoinositides (PPIs) are essential phospholipids located in the cytoplasmic leaflet of eukaryotic cell membranes. Despite contributing only a small fraction to the bulk of cellular phospholipids, they make remarkable contributions to practically all aspects of a cell's life and death. They do so by recruiting cytoplasmic proteins/effectors or by interacting with cytoplasmic domains of membrane proteins at the membrane-cytoplasm interface to organize and mold organelle identity. The present study summarizes aspects of our current understanding concerning the metabolism, manipulation, measurement, and intimate roles these lipids play in regulating membrane homeostasis and vital cell signaling reactions in health and disease.